2001
DOI: 10.1159/000047704
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Regional Cerebral Blood Flow Measurement Techniques Improve Noninvasive Detection of Cerebrovascular Vasospasm after Aneurysmal Subarachnoid Hemorrhage

Abstract: Adequate therapy of vasospasm (VS) in patients suffering from aneurysmal subarachnoid hemorrhage critically depends upon early and reliable diagnosis of cerebral hypoperfusion. The objective of the present study was to evaluate the usefulness of quantitative regional blood flow (rCBF) analysis as an adjunct in noninvasive prediction of VS. Therefore, 33 transcranial Doppler sonography (TCD) studies assuming cerebrovascular VS (TCD flow velocity >120 cm/s) were followed by sXe/CT and cerebral panangi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…Correct probe position was confirmed by a computed tomography (CT) scan. In the same setting, a stable xenon CT (sXe-CT) was performed to validate the TD-rCBF measurements (6,9).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Correct probe position was confirmed by a computed tomography (CT) scan. In the same setting, a stable xenon CT (sXe-CT) was performed to validate the TD-rCBF measurements (6,9).…”
Section: Methodsmentioning
confidence: 99%
“…The diagnostic work-up for vasospasm was further complemented by an sXe-CT study on the day of angiography. In the presence of a mean cerebral blood flow of Ͻ32 mL/100g/ min, hemodynamically relevant cerebral vasospasm was assumed (8,9,11).…”
Section: Methodsmentioning
confidence: 99%
“…7,27 For determination of sXe-rCBF values, a 4.5-min wash-in protocol was applied. Patients received a mixture of medical-grade 30% sXe, 60% O 2 , and balanced air, while a three-level investigation (slice thickness 10 mm) was performed.…”
Section: Stable Xe-enhanced Ct Scanningmentioning
confidence: 99%
“…An advantage of PCT over other screening tests such as transcranial Doppler includes its ability to calculate blood flow throughout the entire territory perfused by a cerebral artery, whereas transcranial Doppler is limited to the evaluation of proximal, large vessels only [7, 10]. Also, increases in blood flow velocities measured by transcranial Doppler do not always correlate with brain perfusion values and do not reliably determine the severity of the patient’s vasospasm [11, 12]. In contrast, different studies have reported PCT thresholds to diagnose and characterize the severity of vasospasm and thus stratify treatment [7,13,14,15].…”
Section: Introductionmentioning
confidence: 99%